Characterization of crystalline GeSn layer on tensile-strained Ge buffer deposited by magnetron sputtering. (October 2018) - Miao, Yuanhao; Wang, Yibo; Hu, Huiyong; Liu, Xiangyu; Su, Han; Zhang, Jing; Yang, Jiayin; Tang, Zhaohuan; Wu, Xue; Song, Jianjun; Xuan, Rongxi; Zhang, Heming
Abstract: High-quality low Sn-content GeSn film has been grown on tensile strained Ge/Si (100) substrate using a physical vapor deposition reactor and no subsequent annealing was carried out after the deposition of the film. High Resolution X-ray diffraction (HR-XRD) measurement was performed to estimate the crystallinity and the residual strain in the Ge layer. Secondary-ion mass spectrometry (SIMS) and X-ray photoelectron spectrometer (XPS) show Sn incorporation of the film is approximately 3%. High-resolution transmission electron microscopy (TEM) and atomic force microscopy (AFM) results show that the crystallinity of the film is quite good and it shows a smooth surface (RMS = 0.744 nm) in 5 µm × 5 µm scan. Raman spectroscopy and photoluminescence (PL) measurements were carried out to study the structural and optical properties of the film. Room-temperature PL of the film was observed and it results in a decrease in the difference between Γ and L valleys of tensile strained Ge (0.21%) from 87 meV to 76 meV, which makes this method promising for obtaining Pseudo-direct bandgap group IV films.